2022
DOI: 10.1021/acs.jnatprod.2c00504
|View full text |Cite
|
Sign up to set email alerts
|

Daphnoretin Arrests the Cell Cycle and Induces Apoptosis in Human Breast Cancer Cells

Abstract: Emerging evidence has shown that daphnoretin, one of the main active ingredients of Daphne giraldii Nitsche, processes antitumor activities in several tumor cells (e.g., colon cancer, lung cancer, cervical cancer, and osteosarcoma). However, the antitumor effect and its mechanism in breast cancer are unexplored. In this study, our data indicated that daphnoretin obviously suppressed the proliferation of breast cancer MCF-7 and MDA-MB-231 cells. Further studies showed that daphnoretin remarkably increased the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It is well documented that activation of Akt induced by the survival factors can suppress apoptosis by phosphorylation [46] . Accumulating evidence suggests that cell proliferation, survival, invasion, migration, apoptosis, glucose metabolism and DNA repair are closely related to the aberrant activation of the phosphatidylinositol 3‐kinase (PI3 K)/protein kinase B (Akt)/mechanistic target of rapamycin (mTOR) signaling [47] . Akt is the key regulator in this pathway, activated Akt can phosphorylate the proapoptotic proteins in the Bcl‐2 family to inhibit their function.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that activation of Akt induced by the survival factors can suppress apoptosis by phosphorylation [46] . Accumulating evidence suggests that cell proliferation, survival, invasion, migration, apoptosis, glucose metabolism and DNA repair are closely related to the aberrant activation of the phosphatidylinositol 3‐kinase (PI3 K)/protein kinase B (Akt)/mechanistic target of rapamycin (mTOR) signaling [47] . Akt is the key regulator in this pathway, activated Akt can phosphorylate the proapoptotic proteins in the Bcl‐2 family to inhibit their function.…”
Section: Resultsmentioning
confidence: 99%
“…In BRCA 4T1 cells, the cells were arrested in the S phase because of the percentage of cells in S phase increased and cells in G1/G0 phase decreased after treating with resveratrol 33 . Daphnoretin could remarkably increase the p21 level and decrease cyclin E and CDK2 levels, and then arrest the cell cycle at the S phase in BRCA 34 . The CDCD20 down-regulation combined with radiation could restrain proliferation, aggravate DNA damage, increase G2/M arrest, and promote apoptosis of HCC cells to a greater extent, and the relative survival fraction of hepatoma cells with p53 mutated Hep3B decreased with increasing irradiation dose 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the inactivation of Pta-ackA signaling significantly increased the rate of glucose consumption, inhibited bacterial growth, and resulted in the death of Staphylococcus aureus , suggesting that the Pta-ackA pathway is critical to bacterial survival ( Sadykov et al., 2013 ). Several studies have shown that daphnoretin (coumarins and derivatives) has significant anti-inflammatory and antitumor effects ( Gu and He, 2012 ; Yu et al., 2019 ; Xie et al., 2022 ). Daphnoretin can suppress IL-1β-induced chondrocyte apoptosis by inhibiting endoplasmic reticulum stress and NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome activation and suppressing osteoarthritis ( Zhou and Wang, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that daphnoretin (coumarins and derivatives) has significant anti-inflammatory and antitumor effects (Gu and He, 2012;Yu et al, 2019;Xie et al, 2022). Daphnoretin can suppress IL-1b-induced chondrocyte apoptosis by inhibiting endoplasmic reticulum stress and NOD-, LRR-and pyrin domain-containing protein 3 (NLRP3) inflammasome activation and suppressing osteoarthritis (Zhou and Wang, 2022).…”
Section: Discussionmentioning
confidence: 99%